River recovery: diagnostic tool and proposal of rehabilitation programs - Acevedo, Ligie Elena Dall’Agnol (2015)
Rivers are subjected to human impacts that transform the natural landscape into areas of environmental degradation, compromising biodiversity and reducing the quality and quantity of available water. Promoting the environmental recovery of watercourses is of paramount importance to the health of ecosystems and sustainability of economic systems alike. In this context, the effectiveness of programs for environmental rehabilitation of aquatic ecosystems requires a tailored restoration approach based on scientific knowledge, which associates physical, chemical, biological, cultural and social interactions. The preparation of a recovery plan requires the association of tools to obtain a diagnostic of the river environmental quality based on analysis of the root causes, associated problems, and possible solutions. Thus, the work described herein aimed to develop a diagnostic guide of river environmental quality to base the implementation of restoration programs. The research was composed of four main stages: I – elaboration of summary matrices correlating river problems, their causes, and possible solutions; II - development of a guide to instruct data collection for application of the tool; III – test application of the products resulting from steps I and II to a segment of the Passaúna river, situated in the Southern Brazilian metropolitan region of Curitiba; IV – data analysis and suggestion of structure for the Passaúna river recovery program. The tool was developed from the organization of scientific and technical data. The information is divided into six summary matrices that relate the root and immediate causes of problems, which are: pollution, flood, loss of aquatic biodiversity, loss of riparian zone biodiversity, loss of navigability, and impairment of hydropower generation. Results include the application of the tool in the segment upstream of the Passaúna reservoir, one of the main sources of water supply to Curitiba and its metropolitan region. Considering the river problems identified, some guidelines to elaborate management plans were proposed involving land use, monitoring and environmental education.